2022
DOI: 10.3390/ani12091202
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Milk Fatty Acid Profile and Body Condition Score, Ultrasound Hepatic Measurements and Blood Metabolites in Holstein Cows

Abstract: Dairy cows have high incidences of metabolic disturbances, which often lead to disease, having a subsequent significant impact on productivity and reproductive performance. As the milk fatty acid (FA) profile represents a fingerprint of the cow’s nutritional and metabolic status, it could be a suitable indicator of metabolic status at the cow level. In this study, we obtained milk FA profile and a set of metabolic indicators (body condition score, ultrasound liver measurements, and 29 hematochemical parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Plasma AST and ALP are used as indicators to reflect liver damage [ 68 ], and high levels lead to liver damage [ 69 ]. Previous studies reported that ALP showed a positive correlation with PUFA in milk [ 20 ]. The GLB is an important immunological active protein in the plasma [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma AST and ALP are used as indicators to reflect liver damage [ 68 ], and high levels lead to liver damage [ 69 ]. Previous studies reported that ALP showed a positive correlation with PUFA in milk [ 20 ]. The GLB is an important immunological active protein in the plasma [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, GF may be suitable to improve the concentration of milk n-3 PUFAs. In addition, milk fatty acid profile is known to be a fingerprint of the health status of the cow [ 20 , 21 , 22 ], thus flaxseed in the diet can also influence the health of dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…They described an increase in the content of long chain fatty acids (LCFA) accompanied by a reduction in short- and medium- chain fatty acids, similarly to other studies which also strictly controlled diet composition and feed [ 50 ] while others noted changes in unsaturated FA [ 51 ]. A limitation of the present research might be not including the milk FA profile, although some information can be obtained from a recent study [ 13 ]. These authors conducted a comprehensive analysis of the milk FA profile performed on a large number of cows ( n = 297) and found no significant association between milk fatty acid (FA) and measured plasma haptoglobin levels [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This factor makes cow´s milk contain the most complex fat of other natural fats [ 4 ]. Due to its importance, Giannuzzi et al observed in a recent study that FA fingerprint could be a cow´s metabolic status indicator [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, fat and protein are genetic components with high heritability [30]. On the other hand, the composition of the fatty acid profile of milk is modified by the process of de novo synthesis, which occurs in the mammary gland of the cow since it has been found that this synthesis has a positive relationship with the formation of medium chain fatty acids and a negative relationship with the formation of long-chain fatty acids [31]. Variations in energy metabolism, such as a negative energy balance after calving and in early lactation, also modify milk fat concentration and lipid profile due to the uptake of non-esterified fatty acids by the mammary gland caused by a high mobilization of reserve fat; however, the percentage of fat will progressively decrease due to the effect of dilution and a decrease in the mobilization of reserve fat [32].…”
Section: Factors That Affect Milk Compositionmentioning
confidence: 99%